A Review on Contextualizing Health Care for Adolescents living with HIV - Agambire, Ramatu; Ansong, Cecilia Ackon (Advances in Social Sciences Research Journal, 2018)
Adolescents Living with HIV (ALHIV) grow up in circumstances quite different from those of their other no-infected counterparts with both psychological, economic, social and sexuality challenges and vulnerabilities. They have an urgent need for improved approaches to address their specific health care needs. Improving outcomes for adolescents and reaching global targets for an AIDS FREE generation by 2030 will require evidence-based interventions and policies. Howbeit, there is a growing area of research in HIV where a considerable amount of efforts is still needed to inform the understanding of what works for this population. Evidence indicates higher rates of loss to follow up, and poor adherence, as well as increased needs for psychosocial support among ALHIV. This population group continues to be underserved by current HIV services and have significantly worse access to and coverage of ART. A number of care models have been designed over the years to improve health outcomes among this group of population. Effective establishment of HIV treatment demands that HIV diagnosis is followed by timely linkage to outpatient care, prompt initiation of anti-retroviral therapy and prophylactic medications when indicated, and subsequent adherence to prescribed medications as revealed in individual studies. Certainty of uptake and successful outcomes demands that, patients must progress through a sequence of steps taking into account environmental, patients predisposition, perceived and enabling factors as well as health behaviour models